DIMENSI PSIKOSOSIAL BERDASARKAN PARTISIPASI DALAM EKSTRAKURIKULER OLAHRAGA DAN KEMAMPUAN MOTORIK (Studi Korelasional di MAN 3 Sukabumi) - Zaitun Fatimatuz Zahra; Asep Sumpena; Jajat Darajat KN (Universitas Negeri Medan, 2025)
This study aims to examine the relationship between participation in sports extracurricular activities and motor skills with psychosocial problems among students at MAN 3 Sukabumi. Adolescence is a developmental phase that is vulnerable to various psychological pressures, making it important to explore the role of physical activity in supporting mental well-being. This research uses a quantitative correlational approach with a sample of 35 students selected through purposive sampling based on specific criteria. The instruments used include the Pediatric Symptom Checklist (PSC-35) to measure psychosocial problems, the Barrow Motor Ability Test to assess motor skills, and a participation questionnaire to measure students’ level of involvement in sports activities. The questionnaire consists of six indicators: attendance, active involvement, having a goal, providing feedback, sharing information, taking responsibility, and perceiving benefits. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 25, through descriptive statistics, normality test, linearity test, and multiple correlation analysis. The results showed a significant negative relationship between participation in sports extracurricular activities and motor skills with students’ psychosocial problems. Participation had a correlation of r = -0.388 (p = 0.021), while motor skills had a correlation of r = -0.409 (p = 0.015). Regression analysis showed that both variables simultaneously contributed 31.9% to psychosocial problems (R² = 0.319; p = 0.002). In conclusion, the higher the level of student participation in sports activities and the better their motor skills, the lower the level of psychosocial problems they experience.